Relational Capital, Work Motivation, and Work Culture as Determinants of Employee Performance at the National Library of the Republic of Indonesia - Rita Suartini; Budi Supriyatno; Azis Hakim (Dinasti International Journal of Digital Business Management, 2025)
This study aims to examine the effects of relational capital, work motivation, and work culture on employee performance at the Center for the Development of Public and Special Libraries, National Library of the Republic of Indonesia, within the context of service transformation and bureaucratic reform. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through a questionnaire distributed to employees and analyzed using SmartPLS software. The results indicate that relational capital, work motivation, and work culture simultaneously influence employee performance, with an adjusted R-square value of 0.534, indicating a moderate predictive power of the model. Partially, work motivation and work culture have a significant positive effect on employee performance, whereas relational capital does not show a significant effect. The effect size (f²) analysis further reveals that work culture exerts the strongest influence, followed by work motivation, while the contribution of relational capital is negligible. These findings suggest that improving employee performance in the National Library environment is more effectively achieved through strengthening work culture and enhancing work motivation as part of human resource development and bureaucratic reform strategies. This study provides empirical evidence and practical implications for human resource management in public-sector library institutions